(untitled) (Global Journal of Medical Research, 2019)
Ceruminous adenocarcinoma of the external auditory canal is a rare malignant tumor originating from the ceruminous gland. Most commonly, presenting with a mass or pain in the outer ear canal of middle-aged patients, but it displays no specific clinical symptoms or signs. With only a few reports documented in the literature, we are presenting a new case of a 37 years old man presented with an advanced malignant ceruminous gland tumor.